2010
DOI: 10.1371/journal.pone.0010240
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Precursor Cells Pre-Exist in Human Breast DCIS and Require Autophagy for Survival

Abstract: BackgroundWhile it is accepted that a majority of invasive breast cancer progresses from a ductal carcinoma in situ (DCIS) precursor stage, very little is known about the factors that promote survival of DCIS neoplastic cells within the hypoxic, nutrient deprived intraductal microenvironment.Methodology and Principal FindingsWe examined the hypothesis that fresh human DCIS lesions contain pre-existing carcinoma precursor cells. We characterized these cells by full genome molecular cytogenetics (Illumina HumanC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
144
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 54 publications
11
144
0
Order By: Relevance
“…Exposure of cancer cells to an acidic environment plays a crucial function in promoting invasive capacity, metastasis, and resistance to apoptotic-inducing agents. Intriguingly, autophagy was shown to represent a major survival mechanism for cytogenetically abnormal neoplastic ductal carcinoma in situ cells (65). The capacity of these cells to form spheroids and generate tumors in SCID mice was abrogated upon treatment with the autophagy inhibitor chloroquine.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of cancer cells to an acidic environment plays a crucial function in promoting invasive capacity, metastasis, and resistance to apoptotic-inducing agents. Intriguingly, autophagy was shown to represent a major survival mechanism for cytogenetically abnormal neoplastic ductal carcinoma in situ cells (65). The capacity of these cells to form spheroids and generate tumors in SCID mice was abrogated upon treatment with the autophagy inhibitor chloroquine.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, current research has shown that while DCIS is non-invasive and clinically defined as "pre-cancerous," these types of lesions do indeed possess carcinoma precursor cells. 20,21 In a recent review, Espina and Liotta 22 address the malignant nature of DCIS and postulate that the stressful, hypoxic intraductal niche selects for the survival and expansion of a subset of genetically abnormal malignant progenitor cells. In accordance with this notion, our data offers activation of signaling pathways and suppression of Bim, Bmf and anoikis by hypoxia as means to enhance cell survival in conditions of low adhesion, such conditions exhibit a significant degree of architectural disorganization as compared to structures formed under normoxic conditions.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…These concentric spheroid regions are generated by the gradients of nutrients, oxygen and growth factors that produce distinctive microenvironments within the tumor mass that are associated with in the build-up of acidic metabolic waste and hypoxic condition in the tumor core. Researchers have suggested that similar biophysical parameters may define the microenvironment of solid tumors in vivo and may account for some aspects of therapeutic sensitivity to chemotherapy and radiation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research studies by Espina et al [19] have shown that ex vivo organoid cultures of breast ductal carcinoma in situ (DCIS) spontaneously produce hundreds of spheroids in the first several weeks in culture that are capable of anchorage independent growth, stromal invasion and tumorgenicity in SCID mice. Moreover, these researchers observed that most of the organoid cultures of DCIS displayed microcalcification, which has been linked to the presence of high grade DCIS by mammography [20].…”
Section: Introductionmentioning
confidence: 99%